Extraction of Pectin from Cui Lemon (Citrus microcarpa) and Its Application in Pineapple Jam - Rompas, Veckie Frankie; Mamuaja, Christine F.; Suryanto, Edi (Pascasarjana Unsrat, 2016)
Cui lemon (Citrus microcarpa Bunge) is a type of small citrus variety that is widely available in North Sulawesi. It is very popular as a preservative and deodorizing agent of fishy odor in fish products, and it is used in traditional chilly sauce